2014
DOI: 10.1002/jib.115
|View full text |Cite
|
Sign up to set email alerts
|

Corn grist adjunct - application and influence on the brewing process and beer quality

Abstract: In the brewing industry, barley malt is often partially replaced with adjuncts (unmalted barley, wheat, rice, sorghum and corn in different forms). It is crucial, however, to preserve constant quality in the beer to meet the expectations of consumers. In this work, how the addition of corn grist (10 and 20%) influences the quality of wort and beer was examined. The following parameters were analysed: wort colour, dimethyl sulphide (DMS) and protein content, non-fermentable extract, extract drop during fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 23 publications
2
32
0
3
Order By: Relevance
“…The L value increased in proportion to the amount of adjuncts (rice, wheat and corn) ( p < 0.05). This can be associated with a decreased amount of nitrogen compounds being present for Maillard reactions, according to Poreda et al . For this reason, potato‐added samples showed the opposite result.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The L value increased in proportion to the amount of adjuncts (rice, wheat and corn) ( p < 0.05). This can be associated with a decreased amount of nitrogen compounds being present for Maillard reactions, according to Poreda et al . For this reason, potato‐added samples showed the opposite result.…”
Section: Resultsmentioning
confidence: 95%
“…This can be seen as a reason why adjuncts are used in brewing, as beer consumption has kept increasing and consumption propensities have changed in pursuit of diversity. Moreover, adjuncts are easy to obtain from the local markets and are less expensive than barley, thus reducing the ingredient costs . However, the addition of un‐malted adjuncts using a simple infusion mashing method requires the pre‐gelatinization of the starch in the adjuncts, which increases the expense owing to the necessity of a cereal cooker installation .…”
Section: Introductionmentioning
confidence: 99%
“…When brewing on an industrial scale, it is common to add specialty malts or brewing adjuncts in small quantities to an existing product to obtain a desired new colour or flavour profile. Such an approach leverages existing infrastructure, representing a more economical path to new products . Following the above process, B11 would be produced by augmenting B7 with specialty malts and adjuncts to develop the colour and flavour associated with an amber ale.…”
Section: Resultsmentioning
confidence: 99%
“…The work by Johnston et al . , showed that after fermentation most of the AFB 1 was found in solids (13%) . Numerous reports also showed that radiolabelled mycotoxins such as AFB 1 can bind to solid particles in an aqueous solution .…”
Section: Fate Of Mycotoxins During the Brewing Processmentioning
confidence: 99%
“…In beer production, the basic ingredients comprise water, barley malt, hops and yeast . In addition, adjuncts such as unmalted cereal grains (wholly or in part) can be utilised . Commonly used adjuncts include maize, wheat, barley, rice, sorghum and syrups .…”
Section: Introductionmentioning
confidence: 99%